Structure of Professional Competence Development of Future Fine Art Teachers: Integration of Technology, Method and Competence - Bolbekovich, Nusharov Bobir (Indonesian Journal Publisher, 2024)
The article gives the data about the structure of proficient competence of advancement: integration of innovation, strategy and competence. It was noted that within the development of professional competence, via the proficient characteristics, educational support of the instructive prepare based on prerequisites of qualification, and the determination of personal approaches to the execution of the educational process are vital. This research investigates the structure of professional competence development in future fine art teachers with a focus on the integration of technology, teaching methods, and subject competence. Qualitative research methods were employed to gain an in-depth understanding of how these factors interact to shape professional competence. Data were collected through classroom observations, interviews with faculty and students, and document analysis. Findings indicate that the integration of technology not only enhances the effectiveness of learning but also enriches students' artistic experiences. Innovative teaching methods, such as project-based learning and student collaboration, also play a crucial role in developing pedagogical and artistic skills. Furthermore, a strong subject competence in fine arts was identified as a key factor in shaping quality art teachers. Implications for curriculum development and art teacher training are discussed. This study provides valuable insights into integrating technology, methods, and subject competence in the formation of professional competence in future fine art teachers.